Evolution of the Fermi surface of Weyl semimetals in the transition metal pnictide family - Liu, Z. K.; Yang, L. X.; Sun, Yan; Zhang, T.; Peng, Han; Yang, H. F.; Chen, C.; Zhang, Yi; Guo, Y. F.; Prabhakaran, Dharmalingam; Schmidt, M.; Hussain, Zahid; et al. (Nature Materials, 2016)
Topological Weyl semimetals (TWSs) represent a novel state of topological quantum matter which not only possesses Weyl fermions (massless chiral particles that can be viewed as magnetic monopoles in momentum space) in the bulk and unique Fermi arcs generated by topological surface states, but also exhibits appealing physical properties such as extremely large magnetoresistance and ultra-high carrier mobility. Here, by performing angle-resolved photoemission spectroscopy (ARPES) on NbP and TaP, we directly observed their band structures with characteristic Fermi arcs of TWSs. Furthermore, by systematically investigating NbP, TaP and TaAs from the same transition metal monopnictide family, we discovered their Fermiology evolution with spin-orbit coupling (SOC) strength. Our experimental findings not only reveal the mechanism to realize and fine-tune the electronic structures of TWSs, but also provide a rich material base for exploring many exotic physical phenomena (for example, chiral magnetic effects, negative magnetoresistance, and the quantum anomalous Hall effect) and novel future applications.
CRIS-Team Scopus Importer:2023-03-20